Development of District Civil Service Applications - Ranuharja, Fadhli; Ambiyar; Indarta, Yose; Samala, Agariadne Dwinggo; Ika Parma Dewi (Politeknik Ganesha Medan, 2022)
This study aims to provide the needs for institutions such as urban villages to provide services, information to residents, making it easier to socialize activities and assist in the administration of correspondence permits from the urban village. The new system needs to be implemented in Tanjung Ayun Sakti Village as a solution to overcome obstacles in accessing information and services in Tanjung Ayun Sakti Village. The application of a population service information system can have a fairly good impact and be beneficial for all interested parties. The development of this system uses the PHP programming language, CodeIgniter framework, XAMPP as a database server for simulation on localhost and the SDLC (Software Development Life Cycle) method. From the results of the development of this information system, the validity test was carried out by experts, then the practicalists are very good. aims to assist the population service process in the form of sending a permit online.